A numerical experiment with huang algorithm (2007)
It is believed that the Huang method is the best one to solve a system of linear equations in the class of ABS methods. Having presented 10 versions of the Huang method and compared them numerically, we will compare the best version of the Huang method with LU (along with partial pivoting) and QR (through Householder transformations) methods. Numerical results show that all three methods yield approximately similar output in well-conditioned problems while the Huang method works more effectively in ill-conditioned problems.